Cardiopulmonary Exercise Test Parameters in Athletic Population: A Review - Reza Mazaheri (MDPI AG, 2021)
Although still underutilized, cardiopulmonary exercise testing (CPET) allows the most accurate and reproducible measurement of cardiorespiratory fitness and performance in athletes. It provides functional physiologic indices which are key variables in the assessment of athletes in different disciplines. CPET is valuable in clinical and physiological investigation of individuals with loss of performance or minor symptoms that might indicate subclinical cardiovascular, pulmonary or musculoskeletal disorders. Highly trained athletes have improved CPET values, so having just normal values may hide a medical disorder. In the present review, applications of CPET in athletes with special attention on physiological parameters such as VO2max, ventilatory thresholds, oxygen pulse, and ventilatory equivalent for oxygen and exercise economy in the assessment of athletic performance are discussed. The role of CPET in the evaluation of possible latent diseases and overtraining syndrome, as well as CPET-based exercise prescription, are outlined.